Shifting Investment Paradigm of Islamic Higher Education Institution Assets: A Case Study of Portfolio Diversification Amid Global Economic Uncertainty - Ahmad Rozaki Mustofa (CV Kalimasada Group, 2025)
This study aims to analyze the shift in the paradigm of asset investment in Islamic higher education institutions, especially in the context of portfolio diversification amidst global economic exposure. The phenomenon of financial market volatility and macroeconomic turmoil competition adaptation strategies of non-profit institutions such as Islamic universities in managing their investment assets for operational continuity and academic development. The research method used is descriptive qualitative with a case study approach at two leading Islamic universities in Indonesia that have significant investment portfolios. Data were collected through in-depth interviews with financial managers, analysis of financial report documents, and observation of investment practices.